Prediction on crystallization behaviors of blast furnace slag in a phase change cooling process with corrected optical basicity. (1st July 2018) - Ding, Bin; Wang, Hong; Zhu, Xun; He, Xian-Yan; Tan, Yu; Liao, Qiang
Highlights: Corrected optical basicity is adopted to represent the slag component. Correlations to predict crystallization behaviors are obtained. Primary phase appears in the slag is predicted. Critical cooling rate and crystal phase content are predicted. Abstract: Up to now, centrifugal granulation and heat recovery technology is the most feasible one to achieve the simultaneous harvest of high-temperature waste heat and high-quality glassy blast furnace (BF) slag. For the phase change cooling process, both the slag components and the cooling rate play dominate roles in the solidification and crystallization behaviors of BF slag, which guides the determination of operational condition in the centrifugal granulation and heat recovery system. Therefore, an accurate prediction on crystallization behaviors of BF slag with various components is convenient to confirm the optimal cooling condition and is crucial to popularize the technology. In the present study, the corrected optical basicity ( Λcorr ) is adopted to represent the slag component. As the results, a series of correlations between crystallization behaviors (including critical cooling rate, phase type, crystal phase content and crystallization temperature region) and the corrected optical basicity are obtained by fitting the experimental data. Moreover, the correlations are mainly available in the range of Λcorr  = 0.643–0.681, and the theoretical results fit well with the experimental data.